2004
DOI: 10.2166/wst.2004.0775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of C/N ratio on nitrous oxide emission from swine wastewater treatment process

Abstract: To evaluate control parameters for nitrous oxide (N2O) emissions in the swine wastewater treatment process, the N2O emission was compared in the activated sludge from SBRs acclimated in different carbon/nitrogen (C/N) ratios. N2O emission from a denitrification phase was very strongly dependent on C/N ratio of swine wastewater, and the total N2O emission in the operating condition of BOD5/TN ratio of 2.6 was approximately 270 times greater than that in BOD5/TN ratio of 4.5. However, the effect of C/N ratio on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 0 publications
7
30
1
1
Order By: Relevance
“…Similar observations have also been reported by Kishida et al [85]. A pure culture study with A. faecalis shows that when carbon sources are limiting, N 2 O formation increases by 32-64%, while N 2 production decreases significantly [84].…”
Section: Key Process Conditions Leading To Nitrous Oxide Emissionssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar observations have also been reported by Kishida et al [85]. A pure culture study with A. faecalis shows that when carbon sources are limiting, N 2 O formation increases by 32-64%, while N 2 production decreases significantly [84].…”
Section: Key Process Conditions Leading To Nitrous Oxide Emissionssupporting
confidence: 89%
“…On the contrary, it is reported in full-scale studies that only little N 2 O generation and emission is observed regardless of carbon deficiency or sufficiency in anoxic zones or aerobic zones [14]. The nitrogen or helium sparging used to induce anoxia in the laboratory scale studies [84,85] may have contributed to the discrepancy between the observation in laboratory scale and full-scale studies. The continuous sparging may have stripped off the dissolved N 2 O to render it unavailable for further reduction to N 2 .…”
Section: Key Process Conditions Leading To Nitrous Oxide Emissionsmentioning
confidence: 92%
“…While the N2O emission factor changed a little, it decreased with increasing C/N ratios, which had also been observed in some previous studies with nitrate as the electron acceptor [35]. Alinsafi et al [36] obtained that during denitrification with NO3-N as the electron acceptor, a low C/N ratio caused NO2-N accumulation, inhibited N2O reductase and induced N2O emissions.…”
Section: Effect Of C/n Ratios On N2o Emissions During Denitrificationsupporting
confidence: 73%
“…At the same storage temperature, ventilation rate, and storage depth, the much lower COD/N ratio of 1.6:1 in BDE might be the primary reason for the higher N 2 O emissions, as compared with RLM, which had a much higher COD/N ratio of 6.8:1. The results of this experiment were consistent with the observations of Wu et al (2009) and Kishida et al (2004), who reported that N 2 O emissions depended fundamentally on the influent COD/N ratio. Wu et al (2009) compared the effects of five COD/N ratios (0:1, 2:1, 5:1, 10:1, and 20:1) on N 2 O emissions from microcosm wetlands.…”
Section: Ch 4 and Co 2 Emissions From Rlm And Bdesupporting
confidence: 91%